PENGARUH PERSEPSI KARIR, PENGETAHUAN PERPAJAKAN, MOTIVASI DAN KEPERCAYAAN DIRI TERHADAP MINAT BERKARIR DI BIDANG PERPAJAKAN (STUDI PADA MAHASISWA AKUNTANSI PERPAJAKAN POLITEKNIK NEGERI LAMPUNG) - Handayani, Refti Puput; Dewi, Anita Kusuma; Kurniawan, Umarudin (LPPM Universitas Bina Bangsa, 2025)
This study aims to determine the effect of career perceptions, taxation knowledge, motivation and self-confidence on career interest in taxation (Study on Tax Accounting Students of Lampung State Polytechnic). The population in this study included active students of Lampung State Polytechnic Tax Accounting study program, Department of economics and business who were still active until 2024. The research sample was determined through purposive sampling method using the criteria of active students of Lampung State Polytechnic tax accounting study program who had passed semester 3 (three) and were not on unilateral leave, so that the sample size was 200 respondents. Research data obtained through questionnaires. Data analysis procedures are carried out using Partial least Square (PLS) software. Testing consists of a measurement model (Outer Model) and a structural model (Inner Model). The results showed that career perceptions had no significant effect on career interest in taxation, while taxation knowledge, motivation and self-efficacy had a positive and significant effect on career interest in taxation.